Sifat-Sifat Tanah pada Berbagai Tingkat Kebakaran Lahan Gambut di Desa Rimbo Panjang Kecamatan Tambang - Hermanto, Hermanto; Wawan, Wawan (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The study aims to determine the physical, chemical, and biological,properties of peat soil on several level of firein Kampar regency. The research was conducted from March to April 2017 in Rimbo Panjang Village, Tambang District, Kampar Regency, Riau Province and Soil Science Laboratory, Faculty of Agriculture, University of Riau. The research was conducted by survey in the field, determining the sample point using Purposive Sampling Method. The soil samples were taken from 3 locations ie. the land with heavy, medium and light fire level and control (non-burning / natural forest) and used as treatment and 3 replications to obtain 12 units of experiment. Soil samples were analyzed soil physical and chemical characteristics. The results showed the physical and chemical characteristics of the soil undergoing changes and categorized as broken.Keywords: fire, peat land damage, soil physical and chemical characteristics